FTIR-METABOLOMICS TO CORRELATE SORGHUM’S CHEMICAL PROFILE AND HCT-116 CYTOTOXICITY CHANGES DURING RICE-ANALOGUE PRODUCTION - Nancy Dewi Yuliana; Endang Prangdimurti; Didah Nur Faridah (Jurnal Teknologi dan Industri Pangan, 2018)
Rice-analogue (RA) made from sorghum (Sorghum bicolor L. Moench) has recently been popular in Indonesia for its potential as an alternative staple food besides rice. Sorghum has many phytochemicals with various functional properties including those which correlate to anticancer activity. The RA production in-volves several steps; polishing, milling, mixing, extruding, and oven drying. This study used FTIR based metabolomics to identify if these steps affect sorghum phytochemicals composition and its cytotoxicity acti-vity against HCT-116 cell lines in-vitro. It was discovered that sorghum cytotoxic activity was relatively sta-ble during the process. The RA final product (oven dried RA) showed higher activity (90.85%) as compared to other samples taken from previous step (2000 ppm dose). The correlation between FTIR profile and cytotoxic activity of RA was analyzed using one of the multivariate data analysis method namely orthogonal projection to the least square (OPLS). By comparing the OPLS data with FTIR data of compounds reported to be found in sorghum, it is shown that typical FTIR patterns for phenolic compounds particularly ferulic acids, p-coumaric acid, and procyanidins, as well as phytosterols, were highly correlated with RA’s cytotoxic activity. The signals were found to be dominant in the most active sample (oven dried RA). It can be concluded that sorghum phytochemicals responsible for its cytotoxic activity were not affected by processing steps, therefore RA is potential to be promoted as alternative func-tional staple food in Indonesia.